Neonatal Resuscitation Practice and Associated Factors among Health Care Workers in Public Health Facilities in West Guji Zone, Southern Ethiopia - Zelalem Wayessa; Boko Safayi; Fitsum Demisie; Girma Tufa Melese; Amana Bonkiye; Belda Beyene (Mashhad University of Medical Sciences, 2024)
Background: Although neonatal resuscitation has the potential to prevent neonatal mortality rates, several factors hinder it is effectiveness. This study aimed to assess the neonatal resuscitation practice and associated factors among health workers in public health facilities in West Guji zone, Oromia, Ethiopia 2021.Methods: A facility-based cross-sectional study design was conducted from February 01 to March 30/2021. Data were collected with a structured self-administered questionnaire and observational checklist. Finally, a convenience sampling technique was employed to select 407 study participants. Binary and Multivariable logistic regression analyses were conducted with 95% confidence intervals and statistical significance is declared at P<0.05.Results: Out of the 407 sampled study population, 402 healthcare workers were involved in the study with a 98.7% response rate and 270 (67.2%) of healthcare workers had good practice in neonatal resuscitation with a 95% confidence interval of 62.6% to 71.8%.  Factors associated with neonatal resuscitation practice were the age of health care workers who are 30 to 34 (AOR= 3.52, 95%CI; 1.27 - 9.74) and 35 to 39 years AOR= 4.00, 95%CI; 1.24 -12.97), work experience (AOR= 5.72, 95%CI; 2.72 - 12.03, training on neonatal resuscitation (AOR=3.6,95%CI;2.16-6.00), availability of neonatal resuscitation guidelines (AOR= 2.29, 95%CI; 1.13 - 4.69), knowledge status (AOR=1.82, 95%CI; 1.0 -3.10), and attitude of healthcare workers towards neonatal resuscitation(AOR=2.18, 95%CI; 1.37 -3.48). Conclusion: The finding shows the neonatal resuscitation practice was low compared with others. Factors associated with neonatal resuscitation practice were identified.  Health institutions should organize healthcare providers on neonatal resuscitation by giving on-the-job training, providing guidelines, and supervising all health facilities to produce competent healthcare workers and reduce neonatal mortality and morbidity.